The Change-Inventory for Career Counseling – An Instrument for Measuring Counseling-Correlated Changes - Toggweiler, Stephan; Künzli, Hansjörg (Frontiers in Psychology, 2020)
Psychometric properties of a 23-item inventory that measures five correlates of career counseling for evaluation purposes are presented. The dimensions were developed bottom-up. The construction sample consisted of 3316 adult clients of public career counseling services in Switzerland, who were assessed within a naturalistic multicenter evaluation study with pre-post design. The inventory proved reliable (Cronbach’s Alpha between .72 and .82, McDonnald’s Omega between .73 and .81). Concerning validity, the dimensions were supported by exploratory and confirmatory factor analysis (CFI = .910, SRMR = .044, RMSEA = .056). Configural, metric and scalar measurement invariance of gender (female vs. male) and age groups (< 30 vs. ≥ 30 years) was also supported. Pre-post changes are medium to large. Practical use and theoretical localization among related German-language instruments are discussed.